2008
DOI: 10.1128/cvi.00278-07
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Type III Secretion System-Based Pseudomonas aeruginosa Live Vector for Antigen Delivery

Abstract: During the last few years, the use of type III secretion system-based bacterial vectors for immunotherapy purposes has been assessed in various applications. We showed that a type III secretion-based Pseudomonas aeruginosa vector delivering the ovalbumin (OVA) antigen induced an efficient specific CD8 ؉ T-lymphocyte immune response against OVA-expressing cells. Because of the intrinsic toxicity of the vector, further virulence attenuation was needed. Therefore, we explored the effects of the deletion of quorum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In this regard, nontoxic B subunits of bacterial toxins such as Shiga or anthrax toxins have been used to deliver diverse cargos and have been classified (depending on the attached components) as oncotoxins, mitotoxins, or immunotoxins (34,35). Moreover, bacterial T3SS have already been engineered to deliver fusion proteins to their sites of action for vaccination and the treatment of inflammatory diseases, cancer, neurodegenerative diseases, intracellular infections, or chronic viral infections (36)(37)(38).…”
mentioning
confidence: 99%
“…In this regard, nontoxic B subunits of bacterial toxins such as Shiga or anthrax toxins have been used to deliver diverse cargos and have been classified (depending on the attached components) as oncotoxins, mitotoxins, or immunotoxins (34,35). Moreover, bacterial T3SS have already been engineered to deliver fusion proteins to their sites of action for vaccination and the treatment of inflammatory diseases, cancer, neurodegenerative diseases, intracellular infections, or chronic viral infections (36)(37)(38).…”
mentioning
confidence: 99%
“…Indeed, auxotrophic mutants for amino acids are also avirulent and have been proposed as possible live vectors for antigen delivery (Epaulard et al . ).…”
Section: Regulatory Network Connecting Environmental Signals To Biofmentioning
confidence: 97%
“…We previously showed that there were high levels of secretion when each of the following reporter proteins was fused with the 54 N-terminal amino acids of ExoS: P. aeruginosa inhibitor of vertebrate lysozyme (IVY), Pseudomonas putida catechol 2,3-dioxygenase, and green fluorescent protein (4). In the present study, we checked whether shorter tags could also allow the secretion of fusion proteins.…”
mentioning
confidence: 90%